2010
DOI: 10.1111/j.1365-2966.2009.15766.x
|View full text |Cite
|
Sign up to set email alerts
|

Constrained simulations of the Local Group: on the radial distribution of substructures

Abstract: We examine the properties of satellites found in high‐resolution simulations of the Local Group (LG). We use constrained simulations designed to reproduce the main dynamical features that characterize the local neighbourhood, i.e. within tens of Mpc around the LG. Specifically, an LG‐like object is found located within the ‘correct’ dynamical environment and consisting of three main objects which are associated with the Milky Way, M31 and M33. By running two simulations of this LG from identical initial condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
126
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(140 citation statements)
references
References 59 publications
13
126
1
Order By: Relevance
“…These simulations have been presented by Gottloeber et al (2010) and several aspects of them have been reported and discussed in recent work (e.g., Libeskind et al 2010;Knebe et al 2011;Di Cintio et al 2012;Benítez-Llambay et al 2013. We discuss briefly the main features relevant to our analysis below and refer the interested reader to those papers for details.…”
Section: The Clues Simulationmentioning
confidence: 93%
“…These simulations have been presented by Gottloeber et al (2010) and several aspects of them have been reported and discussed in recent work (e.g., Libeskind et al 2010;Knebe et al 2011;Di Cintio et al 2012;Benítez-Llambay et al 2013. We discuss briefly the main features relevant to our analysis below and refer the interested reader to those papers for details.…”
Section: The Clues Simulationmentioning
confidence: 93%
“…CLUES runs evolve realizations of the local Universe that mimic their large-scale mass distribution and the tidal fields operating on them. These simulations have been presented in Gottloeber et al (2010) and different aspects of them have been reported in recent work (eg., Libeskind et al 2010;Di Cintio et al 2012;Knebe et al 2011;Benítez-Llambay et al 2013;Yepes et al 2014). We include here a brief description for completeness; full details may be consulted in the above references or in the webpage 3 of the project.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Only particles between 5 h −1 Mpc and 80 h −1 Mpc from the observer, which is placed at the right distance from the Virgo cluster, are taken into account. A proper description of the density field in the innermost 5 h −1 Mpc, although affected by random density fluctuations at this scale, would require a higher resolution simulation to be resolved properly (as in Libeskind et al 2010). Thus this region empty of massive large structures is not considered here.…”
Section: Constrained Simulations Of the Local Universementioning
confidence: 99%